Comparison of Four Chromogenic Media and Hektoen Agar for Detection and Presumptive Identification of Salmonella Strains in Human Stools - Perez, J. M. (American Society for Microbiology, 2003)
Several chromogenic media have been developed to enhance the specificity of Salmonella detection. We compared the performance of four commercial chromogenic media—namely, ABC medium (Lab M. Ltd., Bury, United Kingdom), COMPASS Salmonella agar (Biokar Diagnostics, Beauvais, France), CHROMagar Salmonella agar (CHROMagar Company, Paris, France), and SM ID agar (bioMerieux, Marcy l'Etoile, France)—with conventional Hektoen medium. Nine hundred sixteen stool samples from inpatients at three hospitals were cultured, in parallel, on the five media, both by direct inoculation and after selective enrichment in selenite broth. Sixty-four Salmonella strains with 12 serotypes were isolated on at least one medium. After 48 h of incubation, sensitivity before and after enrichment was 62.5 and 89.1% with ABC medium, 77.1 and 93.8% with COMPASS agar, 66.7 and 89.1% with CHROMagar, 68.8 and 85.9% with SM ID agar, and 85.4 and 98.4% with Hektoen agar, respectively. Broth enrichment and prolonged incubation (48 versus 24 h) increased the sensitivity of all five media. Only one strain was not isolated on Hektoen agar. The number of false-positive isolates was higher with all five media after enrichment in selenite broth and after incubation for 48 h compared to 24 h. The specificity of the four chromogenic media was better than 91% after incubation for 24 h (77.7% with Hektoen agar) and better than 84% after incubation for 48 h (74.8% with Hektoen agar). This higher specificity reduces the need for confirmatory tests, thereby cutting technical time and reagent requirements. Both COMPASS agar and CHROMagar Salmonella, which after simple additional tests showed close efficiencies (96 and 97%, respectively), can be recommended as single-plate media of choice for the detection and presumptive identification of salmonellae in stools.